THYROID FUNCTION ABNORMALITIES: CONNECTING THE DOTS BETWEEN GENETICS AND CLINICAL PRESENTATION - Latib, Adilah Zulaikha Abd; Kum, Yik Zhi; Othman, Siti Nabilah Atiqah; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Subclinical hyperthyroidism presents with low or undetectable levels of thyroid stimulating hormone (TSH), alongside normal levels of free thyroid hormones (fT4 and fT3). While certain individuals may not show any symptoms, others may experience hyperthyroid symptoms like palpitations, weight loss, and heat intolerance. Early recognition and prompt appropriate management are crucial to prevent potential complications, including atrial fibrillation, osteoporosis, and progression to overt hyperthyroidism. CASE A 59-year-old female was referred to our endocrine clinic due to abnormal thyroid function tests (TFTs) revealing subclinical hyperthyroidism. She was asymptomatic. Her thyroid function tests 5 years ago showed similar results, however, she had not received proper consultation or treatment during that time. She has no significant medical history. She has been in menopause since 50 years old with regular menses before that. She had five pregnancies, four of which were preterm, with her eldest child having cerebral palsy and her fourth child deceased due to prematurity. Two of her children have hyperthyroidism. One son is on carbimazole while one daughter has subclinical hyperthyroidism. A repeat thyroid function test still showed suppressed TSH level of 0.04 m IU/L and normal FT4 level of 13.2 pmol/L and free triiodothyronine (fT3) level of 4.3 pmol/L. Molecular studies showed polymorphism of exon 3 of the TSHR gene from the son. CONCLUSION In conclusion, this case report emphasized the need for thorough evaluation and appropriate management of abnormal thyroid function tests, particularly in the presence of familial clustering. Early recognition and treatment can prevent potential complications and improve patient outcomes. Additionally, the potential role of genetic factors, such as polymorphisms in exon 3 of the TSHR gene, should be considered in cases of familial clustering of thyroid disorders. Genetic testing and clinical correlation may be necessary for a comprehensive assessment and management of thyroid disorders associated with genetic polymorphisms.